FOREIGN AND DOMESTIC EXPERIENCE OF PREPARING FUTURE SOCIAL WORKERS TO WORK WITH PERSONS WHO HAVE SPECIAL EDUCATIONAL NEEDS - Skachkova, Hanna (Educological discourse, 2018)
In the article analyzes the systems for preparing social workers to work with people who have special educational needs in universities in the US and Canada. There are revealed features of education in schools of social work at Columbia’s, Michigan’s and other universities. There are indicated experience of Great Britain, France and Germany in preparing future social workers for working with people with special educational needs. In the article considered programs that offer foreign universities in the preparation of future social workers who wish to work with persons with special educational needs. There are described curricula of the higher educational institutions of these countries, which prepare future qualified social workers to work with persons with special educational needs. There are analyzed reasons for the insufficient preparing of future specialists in the social sphere to work with persons with special educational needs. The general features of the process of teaching students of the specialty "social work" in foreign and domestic universities are indicated, among them the continuity of education, multidisciplinarity of training and the diversity of forms of education. The article shows the distinctive features of the professional training of future social workers for working with people with special educational needs, among which emphasis on practical training in foreign universities, the possibility of choosing a narrow specialization in foreign educational institutions and more stringent conditions for admission.